2016
DOI: 10.1039/c6ra22367b
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical response of platinum nanostructures and application for water detection in transformer oil

Abstract: We report the fabrication of platinum nanostructures on an ITO substrate (Pt-NSs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
1
0
2
Order By: Relevance
“…На рис. 3 В пользу лазерного плавления Au/SiO 2 НС свидетельствуют также численные оценки достигаемых температур в рамках однотемпературной модели нагрева (OTM) [18]. Данная модель применима для наносекундных импульсов, так как за время одного импульса температура возбужденных горячих электронов и решеточной подсистемы успевает эффективно выровняться в каждый момент времени.…”
Section: нелинейно-оптические свойства образцовunclassified
See 1 more Smart Citation
“…На рис. 3 В пользу лазерного плавления Au/SiO 2 НС свидетельствуют также численные оценки достигаемых температур в рамках однотемпературной модели нагрева (OTM) [18]. Данная модель применима для наносекундных импульсов, так как за время одного импульса температура возбужденных горячих электронов и решеточной подсистемы успевает эффективно выровняться в каждый момент времени.…”
Section: нелинейно-оптические свойства образцовunclassified
“…Наночастицы (НЧ) благородных металлов проявляют уникальные нелинейно-оптические свойства благодаря особому механизму взаимодействия с лазерным излучением, связанному с существованием коллективных электронных возбуждений, называемых в литературе локализованными или поверхностными плазмонами, время жизни которых ограничено и определяется электронэлектронной (∼ 10 2 fs) и электрон-фононной релаксацией (до 10 2 ps) [1][2][3][4][5].…”
Section: Introductionunclassified
“…This microwave method produced high crystallinity and well dispersed Pt nanoparticles in a cubic shape with less than 10 nm size range, which resulted in a well-defined absorbance peak at 213 nm due to the plasmonic character. The investigation of their NLO responses has shown that the structures of Pt that related to surface plasmon resonance (SPR) as such provided a contribution to the NLO response [8].…”
Section: Introductionmentioning
confidence: 99%